Implementation of the driver training curriculum in Spain – An analysis based on the Goals for Driver Education (GDE) framework - J. Gabriel Molina; Rafael García-Ros; Esko Keskinen (Pergamon Press, 2025)
The Goals for Driver Education (GDE) framework represents a conceptual outline of the goals to be satisfied in driver education (Hatakka et al., 2002). We aimed to analyze the implementation of the driver training curriculum in Spain, taking this framework as reference; the Spanish driving instructors was the target population from which to gather the information to be analyzed. For this purpose, we developed the DTCI (Driver Training Curriculum Implementation) scale as well as a number of questions concerning the driving instructors' opinions about their own training as instructors, and they were included in a survey that provided information for a probabilistic sample of 676 driving instructors. On the one hand, an analysis of the factor structure of the DTCI scale provided a two-factor solution that fitted the hierarchical levels of the first dimension of the GDE framework; however, no factor differentiation reflected the components of the second dimension of this framework. On the other hand, the survey results suggested that the Spanish driver education system places more emphasis on knowledge and skills related to the operative and tactical aspects of driving, whereas less importance is placed on risk-prevention and self-evaluation skills related to the strategic and personal levels of driving behavior. These results reveal a potential weakness in the driver training curricula from the point of view of the GDE framework and support the application of instructional methods and teaching tools that correct these potential flaws in the training of student drivers.